The Purpose of Remittances – Evidence from Germany - Thomas K. Bauer; Mathias G. Sinning (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper examines the purpose of remittances using individual data of migrants in Germany. Particular attention is paid to migrants' savings and transfers to family members in the home country. Our findings indicate that migrants who intend to stay in Germany only temporarily have a higher propensity to save and save larger amounts in their home country than permanent migrants. A similar picture emerges when considering migrants' payments to family members abroad. The results of a decomposition analysis indicate that temporary and permanent migrants seem to have different preferences towards sending transfers abroad, while economic characteristics and the composition of households in home and host countries are less relevant.
Keywords: F22; D12; D91; 330; International migration; savings; remittances; Rücküberweisung (Migranten); Sparen; Privater Transfer; Deutschland